Evaluation of Complete IELTS Bands 5-6 from Teachers’ Perspectives - Talebi, Zahra; Omidinia, Anita; Khodadoost, Mohammad Reza (Universitas Teknokrat Indonesia, 2024)
This study evaluates the effectiveness of the complete IELTS Bands 5-6 course from teachers' perspective. The course provides comprehensive analysis and practice for the IELTS reading, listening, speaking, and writing papers. The research also investigates teachers' opinions on the course content, structure, and teaching methods. A purposive sampling technique was used to select 40 experienced teachers who had taught IELTS using the textbook for at least five years. Data was collected using an eclectic textbook evaluation checklist, comprising macro (general aspects) and micro evaluation (language skills and structures). Participating teachers completed a questionnaire based on the eclectic checklist. Data analysis followed a mixed method approach, utilizing descriptive statistics. The findings indicate that the complete IELTS Bands 5-6 course effectively prepares candidates for the IELTS exam. Additionally, teachers have positive opinions about the course content, structure, and teaching methods. Overall, this study concludes that the textbook is a valuable resource for both teachers and IELTS candidates. The findings may have implications for IELTS examination and preparation centers, IELTS instructors as well as the candidates.